Labeling of Chromosomes in Cell Development and the Appearance of Monozygotic Twins. (21st June 2015) - Jim, Carol; Berkovich, Simon
Abstract : Understanding the mechanism behind the structure of the internal cellular clock can lead to advances in the knowledge of origins of pairs of monozygotic twins and higher order multiples as well as other biological phenomena. To gain insight into this mechanism, we analyze possible cell labeling schemes that model an organism's development. Our findings lead us to predict that monozygotic quadruplets are not quadruplets in the traditional sense but rather two pairs of monozygotic twins where the pairs slightly differ—a situation we coin quadruplet twins. From the considered model, the probability of monozygotic twins is found to be1 / 2 K, and we discover that the probability of monozygotic quadruplets, or triplets as in the case of the death of an embryo, is1 / 8 K, where K is a species-specific integer representing the number of pairs of homologous chromosomes. The parameter K may determine cancerization with a probability threshold that is approximately inversely proportional to the Hayflick limit. Exposure to some cancerization factors such as small levels of ionizing radiation and chemical pollution may not produce cancer.